Entre l’histoire et la science : le Bois de la Croix après l’an mil - Georges Kazan (Trésor de Liège, 2022)
In my previous article in this series, I explored the origins of the major relics of the Wood of the Cross before the year 1000. This study summarises the basis for the Legend of Helena (which becomes a significant aspect of the later Roman tradition of the Cross) examines the fate of these after that point, as well as the tradition of the relics of the Holy Wood in Rome, while also surveying the major trends in reliquaries used for such objects in the Orthodox East and Latin West.